Diabetes Mellitus: a necessidade de um dispositivo de administração de insulina para crianças e adolescentes - Lucas Renato Tescke (2016)
Diabetes mellitus is a chronic disease in rapid expansion throughout the world, affecting people of any age or gender. This disease affects the pancreas influencing insulin production, and, in some cases, the pancreas stops producing that hormone. Even though there is no cure, the treatment of diabetes consists of daily injections of insulin, which are necessary to control the glycemic levels and prevent future complications. The identification of an opportunity for the development of this project comes from the inexistence of a specific device for administering insulin on children. This study aimed to identify the needs to development a new insulin delivery device for diabetic children allowing to increase the quality life of them. For such, it was studied the history of the disease, the devices available on the market, new technologies for the treatment of this disease and the necessities of the user.